Ecologies of 'Dead' and 'Alive' landmines in the borderlands of Myanmar. (6th July 2022) - Buscemi, Francesco
Abstract: This article deals with a question foregrounded by historian Willem van Schendel in his seminal 2002 article 'Geographies of Knowing, Geographies of Ignorance': how do arms, arms flows, and associated regulatory practices reshape the geometries of authority and power in borderlands? The rich transdisciplinary literature on borderlands has fruitfully deployed van Schendel's insights to re-spatialise areas and states but has devoted scant attention to such question. Drawing from 'new materialist' scholarship in IR and the concept of scale in political geography, the paper argues that fluid and fractionally coherent combinations of weapons as technical objects that come from somewhere, rationalities, and techniques of arms control reproduce multiple scales of territorial authority and struggles over scaled modes of governing violence in borderlands. Such struggles of scales and about scale constantly reconfigure the territorial arenas of authority on violence at the edge of the state. Based on fieldwork in Ta'ang areas of northern Shan State, Myanmar, the article develops an empirical analysis of encounters between explosive devices/landmines and the subjects and spaces they target. Delving into the processes and practices of 'making' and controlling the 'landmine', I find that different socio-political orders confront themselves through rationalities, techniques, and practices of humanitarian arms control via which they navigate/jump across scales, forge new ones, or mobilise multi-scalar alliances. Different types of 'dead' and 'alive' landmines nonetheless defy these attempts at rescaling territorial authority over violence by acting in unforeseen manners at the scale of their own ecologies of violence.